THE QUANTITATIVE DATA COURSE IN THE EXECUTIVE DEVELOPMENT PROGRAM. - Backer, Morton (The Accounting Review, 1961)
Abstract The executive training program has become one of the more interesting post-war developments in business education. A major portion of these program is concerned with the use of quantitative data for business controls and decision-making. Hence Accounting has an important role in these programs. Executive development program is concerned only with the uses of quantitative data as a basis for controls and decision- making, the instructor should avoid depth discussions of the more technical aspects of the disciplines involved. The course in the use of quantitative data should not be regarded as an entity separate and apart from the other courses in the program. Only the relevant elements of accounting, statistical, and economic theory should be employed. Major emphasis should be placed on the planning, control, and decision-making phases of the course. It involves the most careful selection of material. In the context of previous background this article discusses the structuring of the quantitative data course .